Erratum: Sanz del Olmo, N.; et al. Antioxidant and Antibacterial Properties of Carbosilane Dendrimers Functionalized with Polyphenolic Moieties. Pharmaceutics 2020, 12, 698 - Natalia Sanz del Olmo; Cornelia E. Peña González; Daniel Rojas; Rafael Gómez; Paula Ortega; Alberto Escarpa; Francisco Javier de la Mata (MDPI AG, 2021)
Due to an error during production, in [...]